Life-threatening bleeding due to persistent dabigatran effect in a patient with sepsis despite idarucizumab therapy and haemodialysis. Issue 8 (21st August 2019) - Humphries, Kathryn; Huggan, Paul; Stiles, Martin; Martynoga, Robert
Abstract : A 58-year-old man presented with necrotising fasciitis and septic shock requiring urgent surgical debridement. Idarucizumab was used preoperatively to reverse the effects of dabigatran, which he was taking for chronic atrial fibrillation. He developed multiorgan failure including an oliguric acute kidney injury and was given continuous venovenous haemodiafiltration. Adjunctive intravenous immunoglobulin therapy was used in addition to his antibiotic therapy for necrotising fasciitis. Significant clinical and laboratory coagulopathy continued for over 12 days with evidence of a persistent dabigatran effect. Here, we discuss the potential impact of the immunoglobulin therapy, the patient's weight on the degree of redistribution of dabigatran seen and the oliguria in the context of an acute kidney injury on the apparent lack of the effectiveness of idarucizumab.